2013
DOI: 10.1063/1.4817186
|View full text |Cite
|
Sign up to set email alerts
|

Density and anomalous thermal expansion of deeply cooled water confined in mesoporous silica investigated by synchrotron X-ray diffraction

Abstract: A synchrotron X-ray diffraction method was used to measure the average density of water (H2O) confined in mesoporous silica materials MCM-41-S-15 and MCM-41-S-24. The average density versus temperature at atmospheric pressure of deeply cooled water is obtained by monitoring the intensity change of the MCM-41-S Bragg peaks, which is directly related to the scattering length density contrast between the silica matrix and the confined water. Within MCM-41-S-15, the pore size is small enough to prevent the crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 71 publications
0
26
0
Order By: Relevance
“…On one hand, earlier simulation studies by Giovambattista and co-workers [16,65] reported an enhancement of the isothermal compressibility and isobaric thermal expansivity of confined water in model 'hydrophobic' and 'hydrophilic' silica pores. On the other hand, Xu et al [66] and Liu et al [4] have experimentally observed a significant augmentation of the thermal expansivity of confined water in hydrophilic silica pores, while experimental evidence of confined water in hydrophobic activated carbon substrates from Futamura et al [3] suggests a similar enhancement behaviour for the thermal expansivity. …”
Section: Combined Effect Of Surface Strain and Fluid Confinement On Tmentioning
confidence: 91%
See 1 more Smart Citation
“…On one hand, earlier simulation studies by Giovambattista and co-workers [16,65] reported an enhancement of the isothermal compressibility and isobaric thermal expansivity of confined water in model 'hydrophobic' and 'hydrophilic' silica pores. On the other hand, Xu et al [66] and Liu et al [4] have experimentally observed a significant augmentation of the thermal expansivity of confined water in hydrophilic silica pores, while experimental evidence of confined water in hydrophobic activated carbon substrates from Futamura et al [3] suggests a similar enhancement behaviour for the thermal expansivity. …”
Section: Combined Effect Of Surface Strain and Fluid Confinement On Tmentioning
confidence: 91%
“…Extensive effort has been focused on the study of the behaviour of water at water-solid interfaces, including experimental work [1,[2][3][4], theoretical developments [5], and molecular simulation approaches [6][7][8][9]. These efforts have confirmed the generalised view that interfaces can greatly modify the structural and dynamical behaviour of water (or any other fluid for that matter) [10] based on the fact that the presence of a solid surface in an otherwise homogeneous bulk fluid introduces an obvious interaction asymmetry, i.e., between the fluid-surface and the fluid-fluid interactions with the formation of local density perturbations that translate into inhomogeneous distributions (profiles) of fluid properties that eventually decay to their corresponding bulk values, provided that there are no encounters or overlaps with other inhomogeneous regions (e.g., formation of confined regions [11,12]).…”
Section: Introductionmentioning
confidence: 99%
“…Silica-1.5 nm was prepared by calcination of micellar template silica matrices made up of micrometer size grains. Pre-formed β-zeolite kernels (composed of tetraethylammonium hydroxide), NaOH, and fumed silica reacted with decylmethylammonium bromide solution in order to synthesize the silica matrix (Liu et al, 2013 ). The β-zeolite seeds were utilized to make the silica nanopore walls semi-crystalline and resilient to hydrolysis deterioration (Liu et al, 2000 ).…”
Section: Methodsmentioning
confidence: 99%
“…It is now clear that its structural and dynamical properties make it a liquid that stands out from the rest, and its properties make it play a central role in different disciplines, from nanofluidics to biology. 1 The last few years have witnessed a large number of experimental and numerical studies of confined water, both in nanopores [2][3][4][5][6][7] and between planer walls (smooth, crystalline, and amorphous), [8][9][10][11][12][13] seeking to shed light on the changes that take place in its properties compared to bulk water.…”
Section: Introductionmentioning
confidence: 99%